School Literacy Movement Implementation Strategy in Forming Effective Schools in State Elementary School 02 Kalikuda, Adipala District, Cilacap Regency - Ine Kusuma Aryani; Siwi Jatmiko (Green Publisher, 2024)
This study aims to determine the extent of the implementation strategy of the school literacy movement in forming effective schools at SD Negeri 02 Kalikuda, Adipala District, Cilacap Regency. The research method used is a descriptive qualitative method, which examines the natural condition of objects with the researcher acting as the key instrument. The goal of this qualitative research is to provide an in-depth, detailed, and comprehensive depiction of the empirical reality behind the phenomenon. Data were collected through observation and interviews with informants or participants. The research results indicate that the implementation strategy of the School Literacy Movement (GLS) comprises three main stages: the Habituation Stage, which includes activities such as reading for 15 minutes before lessons start, Literacy Thursdays, and building a literacy-rich physical school environment; the Development Stage, involving the creation of reading corners in classrooms, development of other facilities (UKS, canteen, school garden), and creating text-rich materials, as well as fostering a literacy-rich school environment; and the Learning Stage, which includes reading activities for 15 minutes before class with both lesson and non-lesson content, integrating literacy activities into the curriculum, and implementing various comprehension strategies in thematic lessons. The results of this research will be published and presented in international journals or proceedings.